One size does not fit all: a rethink of international law mechanisms in the case of the Lord's Resistance Army in Uganda - Harsant, Angelique; Ellis, Willem (Faculty of Humanities, University of the Free State, 2008)
Abstract not available
Keywords: International law; Ugandan conflicts; Human rights violations; Lord's Resistance Army; Uganda